Electrolyte Imbalance In Acute Stroke: Electrolyte Imbalance In Acute Stroke - Kalyan, Meenakshi; Nahdi, Waleed Khalid; Kanitkar, S.A.; Moharkar, Abhijit; Saha, Rajdeb (National Journal of Integrated Research in Medicine, 2018)
Background: Electrolyte imbalance is an important cause of mortality and morbidity in cerebro vascular accident.Timely treatment can decrease the mortality. Objective: To study the electrolyte disturbances including serum and urinary sodium, potassium and chlorides in acute stroke with its comparison in ischaemic and haemorrhagic stroke. Methods: Serum electrolytes (sodium potassium and chlorides) and urinary electrolytes were investigated in 50 acute stroke patients in a tertiary care hospital.The data was analysed using Chi-square test using SPSS (Statistical package for social science) software. Results: Mean age of the patients was 54years.23 patients (46.0%) had haemorrhagic stroke and 27 (54.0%) had ischaemic stroke. 25 (50.0%) had dyselectrolytaemia which is statistically significant (p = 0.047).10 (37.0%) ischaemic stroke patients and 6 (26.1%) haemorrhagic stroke patients had hyponatremia which is significant (p= 0.048). Conclusion: Hyponatremia was found more in ischemic strokes. [Meenakshi K NJIRM 2017; 8(4):23-26]